2014
DOI: 10.1016/j.mex.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Optimized DPPH assay in a detergent-based buffer system for measuring antioxidant activity of proteins

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…Using the DPPH assay, we demonstrated that antioxidant activity solubilized from plaques and the degree of antioxidant activity indirectly correlated to plaque age (significant ( p , 0.001) decrease in antioxidant activity between days 1-4 and days [17][18][19][20]. Antioxidant activity (normalized % of antioxidant activity [(sample DPPH activity 2 negative control)/full DPPH reduction] Â 100) was maintained at 60-70% over days 1-12, and then stabilized at approximately 30% over days [13][14][15][16][17][18][19][20] (no significant ( p .…”
Section: Antioxidant Activity In Plaque Extracts and In Situmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the DPPH assay, we demonstrated that antioxidant activity solubilized from plaques and the degree of antioxidant activity indirectly correlated to plaque age (significant ( p , 0.001) decrease in antioxidant activity between days 1-4 and days [17][18][19][20]. Antioxidant activity (normalized % of antioxidant activity [(sample DPPH activity 2 negative control)/full DPPH reduction] Â 100) was maintained at 60-70% over days 1-12, and then stabilized at approximately 30% over days [13][14][15][16][17][18][19][20] (no significant ( p .…”
Section: Antioxidant Activity In Plaque Extracts and In Situmentioning
confidence: 97%
“…Antioxidant activity (normalized % of antioxidant activity [(sample DPPH activity 2 negative control)/full DPPH reduction] Â 100) was maintained at 60-70% over days 1-12, and then stabilized at approximately 30% over days [13][14][15][16][17][18][19][20] (no significant ( p . 0.87) change between the days 13-16 and days 17-20, n ¼ 13-20, figure 2c).…”
Section: Antioxidant Activity In Plaque Extracts and In Situmentioning
confidence: 99%
“…Briefly, 150 µL of formulated flavonosomes or PC or QKA or QKA + PC was mixed with 50 µL of 0.1 mM DPPH solution (methanol with 0.3% Triton X-100 v/v). 30 The flavonoids/PC content in carrier, free flavonoids mix, and physical mixture were adjusted to the same concentration as the formulated flavonosomes. Then the solution was incubated at 37°C in the dark for regulated time points at …”
Section: In Vitro Antioxidant Dpph Kineticsmentioning
confidence: 99%
“…Free DPPH radical at a concentration of 0.1 mM dissolved in methanolic solution with 0.3% Triton X-100 v/v was stable for up to 16 hours in the reaction medium. 30 Thus, it allows the compounds to be evaluated in that time range. In this study, we have evaluated the scavenging activity for up to 4 hours at various time points by using individual experimental set for each time point.…”
mentioning
confidence: 99%
“…The DPPH (1, 1-diphenyl-2-picrylhydrazyl) and BSLT (brine shrimp lethality test) are general bioassays for pharmacological activities of active phytochemical components of medicinal plants. The DPPH test is a well established assay for the In vitro determination of antioxidant activity in medicinal plant extracts 7 . BSLT is a general bioassay that appears capable of detecting a broad spectrum of bioactivity present in crude extracts of medicinal plants 8 .…”
Section: Introductionmentioning
confidence: 99%